2021
DOI: 10.1097/md.0000000000025161
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the efficacy of intravitreal dexamethasone implant before and after silicone oil removal

Abstract: Rationale: An intravitreal dexamethasone (IV-DEX) implant is safe and effective for the treatment of macular edemas; however, the efficacy of IV-DEX implants in silicone oil (SO)-filled eyes remains controversial. There is no previous study comparing an IV-DEX implant in the same eye with and without intravitreal SO. Patient concerns: A 72-year-old man with proliferative diabetic retinopathy, macular edema, and rhegmatogenous retinal detachment, treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A case report by Lambat et al 26 described intravitreal bevacizumab to treat CME under SO, resulting in significant improvement of VA and complete resolution of CME within a week of the injection. Another case report by An and Kim 27 described the use of intravitreal dexamethasone implants, which were not effective before SOR but improved VA and CFT after SOR. One notable outlier in our study showed a substantial improvement in logMAR VA from 2.0 to 0.3 despite not receiving any CME-specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A case report by Lambat et al 26 described intravitreal bevacizumab to treat CME under SO, resulting in significant improvement of VA and complete resolution of CME within a week of the injection. Another case report by An and Kim 27 described the use of intravitreal dexamethasone implants, which were not effective before SOR but improved VA and CFT after SOR. One notable outlier in our study showed a substantial improvement in logMAR VA from 2.0 to 0.3 despite not receiving any CME-specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an intravitreal dexamethasone implant (DEX-I) was found to be effective and safe for the treatment of CME after vitrectomy for RRD [ 20 , 21 , 22 , 23 , 24 ] and in SO-filled eyes [ 25 ]. However, in a recent case report, DEX-I showed less effectiveness in the treatment of macular edema in a SO-filled eye than that in an eye after SO removal [ 26 ].…”
Section: Introductionmentioning
confidence: 99%